Sustainable Development Goals (SDGs) Implementation: Youth Ecopreneurship Intention in Waste Plastics Management into Valuable Products in Border Areas - Aloysius Hari Kristianto; Pramatatya Resindra Widya (Fakultas Ekonomi Universitas Kadiri, 2021)
This study is aiming to develop the youth ecopreneurship intention. We evaluate how to process plastic waste into a valuable product as well as maintaining a sustainable environment. This is qualitative type research utilizing participatory and project-based learning methods. This method was chosen so we can objectively explain the feasibility of the use of plastics waste into productive goods. Data is collected using a participatory observation method, in-depth interviews, and documentation techniques. The object of this research is the youth in the border area, especially in Bengkayang. The finding indicated that intention and internal motivation in the youth entrepreneurship for converting plastics waste into valuable products are very positive. It is due to a relatively easy and inexpensive manufacturing process. However, there are external factors, that can negatively influence youth entrepreneurs’ drive, therefore we need to have stimulus and encouragement from outsiders (mentors), training and motivation. There was a tendency for youth to get bored with the long due process, and they want to get quick results immediately. This study only focused on the youth ecopreneurship intention in border areas, therefore it could still be biased. Therefore, further research is needed to provide more complex variables and a bigger number of more varied samples.